Effects of listening comprehension, word recognition, and oral reading fluency on reading comprehension in second-grade students - Ribeiro, Iolanda (2016)
Several studies have provided evidence regarding the importance of listening comprehension, word recognition and oral reading fluency in successful reading comprehension; however, most of the research has been conducted with English language speakers. This study aims to examine the direct effects of these three variables on reading comprehension using a sample of European Portuguese speakers. A sample of 325 second- grade Portuguese students completed the Test of Word Reading, the Reading Fluency Assessment Test, the Test of Listening Comprehension of Narrative Texts and the Test of Reading Comprehension of Narrative Texts. Path analysis showed that listening comprehension, word recognition and oral reading fluency were all significant predictors with unique effects on reading comprehension at this grade level. The combination of all three predictors explained 41% of the variance observed in reading comprehension. The results are discussed in terms of the practical implications and limitations of the study, and guidelines for future research are presented.